Differential proteomic analysis of platelets suggested target-related proteins in rabbit platelets treated with Rhizoma Corydalis. (1st January 2017) - Li, Chun-Hong; Chen, Cen; Zhang, Qian; Tan, Chen-Ning; Hu, Yuan-Jia; Li, Peng; Wan, Jian-Bo; Feng, Gang; Xia, Zhi-Ning; Yang, Feng-Qing
Abstract: Context: Corydalis yanhusuo W.T. Wang (Papaveraceae) ( Rhizoma Corydalis ) showed inhibitory effects on rabbit platelet aggregation induced by ADP, thrombin (THR) or arachidonic acid (AA). Objective: This study separates and identifies the possible target-related platelet proteins and suggests possible signal cascades of RC antiplatelet aggregation. Materials and methods: Based on comparative proteomics, the differentially expressed platelet proteins treated before and after with 50 mg/mL RC 90% ethanol extract (for 15 min at 37 °C) were analyzed and identified by two dimensional gel electrophoresis (2-DE) and MALDI-TOF-MS/MS. To further verify the possible signalling pathways of RC antiplatelet aggregation function, the concentration of calcium (Ca 2+ ) was measured by Fura-2/AM fluorescence (Ex 340/380 nm, Em 500 nm) (RC final concentrations of 0.0156–0.1563 mg/mL), the levels of P-selectin and cyclic guanosine monophosphate (cGMP) were quantified by ELISA (OD. 450 nm) (RC final concentrations of 0.0156–1.5625 mg/mL), and the 5-hydroxytryptamine (5-HT) level was measured using ortho -phthalaldehyde (OPT) fluorescence (Ex 340 nm, Em 470 nm) (RC final concentrations of 0.3125–1.5625 mg/mL). Results: The expression of 52 proteins were altered in rabbit platelets after the treatment and the MALDI-TOF-MS analysis indicated that those proteins include 12 cytoskeleton proteins, 7 cell signalling proteins, 3 molecular chaperone proteins, 6 proteins related to platelet function, 16 enzymes and 7 other related proteins. Furthermore, RC extract could decrease the levels of 5-HT [inhibition rate of 96.80% ( p < 0.05, vs . THR-activated group) treated with 0.7813 mg/mL of RC], Ca 2+ [172.73 ± 5.07 to 113.56 ± 5.46 nM ( p < 0.001, vs . THR-activated group) treated with 0.0313 mg/mL of RC] and P-selectin [13.48 ± 0.96 ng/3 × 10 8 to 11.64 ± 0.17 ng/3 × 10 8 ( p < 0.05, vs . THR-activated group) treated with 0.0156 mg/mL of RC], and increase in cGMP level [38.93 ± 0.57 to 50.26 ± 4.05 ng/3 × 10 8 ( p < 0.05, vs . THR-activated group) treated with 1.5165 mg/mL of RC] in ADP (10 μmol/L), THR (0.25 u/mL) or AA-(0.205 mmol/L) activated rabbit platelets. Discussion and conclusion: The present study indicated that P2Y12 receptor might be one of the direct target proteins of RC in platelets. The signal cascades network of RC after binding with P2Y12 receptor is mediating Gαi proteins to activate downstream signalling pathways (AC and/or PI3K signalling pathways) for the inhibition of platelet aggregation.